Thermal behaviour of brake pad light rail transit / Mohd Zaki Bahrom - Bahrom, Mohd Zaki (2009)
Material specification and operating temperature are very important for product performance especially for tran sportation application such as brake pad material. For light rail brake pad, other than strength, wear and friction , thermal stability is also an important property to investigate due to temperature variation during operation. Hence, four sample differences of laboratory formulation are used to study the therm al stability of brak e pad material. The thermal behaviour is determined by therm al gravimetric and differential thermal analyser which are heated up to 1000°C were used in combination with evolve gas analysi s. Scanning electron microscope equipped with energ y disper sive x-ray and quantitative x-ray flore scenc e techniques are used to determine the element present in formulated brake pad samples. Friction and wea r test was conducted to determine the thickne ss losses. A brake pad is basicall y a mixture of iron (Fe), carbon (C), fibre , lubricant material and binder system. The materials distributed in samples were found to be nonhomogeneou s. On EDAX surface mapping, iron elements in higher contents were present compared to carbon and other materials. The selected raw material are analysed to have record data on its composition and characteristic especially thermal prop ertie s, maximum decomposition temperatures (Tmax dec) were evaluated from DTG (Differential Thermal Gravimetric) curve and analysed as to whether there is any decomposed by products formed . The formulations of brake pads material s weight loss are around 5% to 10%. The friction and wear test result s showed different value of friction coefficient (u) in the range 0.2 to 0.5. The lowest thickness loss is around 1.44 % and the highest thickness loss is around 5 %. Higher thickne ss loss means shorter brake pad life and thus , incurred more material and maintenance cost.